Textbook assessment and religious education efforts: how to achieve religious moderation in schools? - Sihombing, Adrianus Adison; Fatra, Maifalinda; Suhaib, Abdul Quddus; Hussain, Nazar (Atthulab: Islamic Religion Teaching and Learning Journal, 2023)
This article delineates the process of evaluating the substance of religious education literature affiliated with Islam, Catholicism, Protestantism, Hinduism, and Buddhism. Moderation is regarded as a fundamental component of a pluralistic and multicultural society. Beyond that, its primary objective is to prevent division within the nation and address the issue of intolerance in textbooks. By employing a qualitative-descriptive-exploratory conceptual framework and conducting focus group discussions (FGDs) with multiple experts, this writing method is informed by meticulous observation and reading of religious education texts spanning grades kindergarten to high school. This research demonstrates that religious textbooks continue to include material that has the potential to incite violence, prejudice, and hostility. Furthermore, this analysis establishes textbook evaluation as a "bridge" to achieving religious moderation in madrasas and institutions. The independent assessment team and the book evaluation committee were both interviewed. This study emphasises the significance of providing authors and publishers with writing guidelines, training, and mentoring to ensure that the quality of textbooks produced aligns with the content embraced by the nation's norms, values, and culture. Â Artikel ini menguraikan proses penilaian substansi literatur pendidikan agama yang berafiliasi dengan Islam, Katolik, Protestan, Hindu, dan Budha. Moderasi dianggap sebagai komponen mendasar dari masyarakat pluralistik dan multikultural. Selain itu, tujuan utamanya adalah untuk mencegah perpecahan dalam bangsa dan mengatasi masalah intoleransi dalam buku pelajaran. Dengan menggunakan kerangka konseptual kualitatif-deskriptif-eksploratif dan melakukan diskusi kelompok terfokus (FGD) dengan berbagai ahli, metode penulisan ini didasarkan pada observasi dan pembacaan yang cermat terhadap teks-teks pendidikan agama mulai dari tingkat taman kanak-kanak hingga sekolah menengah atas. Penelitian ini menunjukkan bahwa buku teks agama masih memuat materi yang berpotensi memicu kekerasan, prasangka, dan permusuhan. Lebih lanjut, analisis ini menjadikan evaluasi buku teks sebagai â€œjembatanâ€ pencapaian moderasi beragama di madrasah dan lembaga. Tim penilai independen dan panitia evaluasi buku sama-sama diwawancarai. Studi ini menekankan pentingnya memberikan pedoman penulisan, pelatihan, dan pendampingan kepada penulis dan penerbit untuk memastikan bahwa kualitas buku teks yang dihasilkan sejalan dengan konten yang dianut oleh norma, nilai, dan budaya bangsa.